The culture of equity in Restoration and eighteenth-century Britain and America - Fortier, Mark, 1953- (Ashgate, 2015)
Extending the chronological and cultural scope of Fortier's book on equity, which focuses on early modern England, this interdisciplinary study draws on politics, religion, law, literature, and philosophy to argue that equity continued to be a key word throughout the Restoration and 18th century in Britain and America. Fortier asserts that equity is used and contested in many of the major social and political events of the period.